A little chaos [videorecording (DVD)] - Rickman, Alan; Rickman, Alan; Winslet, Kate; Schoenaerts, Matthias, 1977-; Tucci, Stanley
A romantic drama following Sabine, a strong-willed and talented landscape designer, who is selected to build one of the main gardens at King Louis XIV's new palace at Versailles. In her new position of power, she challenges gender and class barriers while also becoming professionally and romantically entangled with the court's renowned landscape artist Andre Le Notre.